The School-Level Curriculum Policy Transfer Process: Learning From A Rural School in Indonesia - Eny Winarti (Bandar Lampung University (UBL), 2013)
Public tends to assume that high scores achievements in a National Exam are strongly related with the success of education. This study was an exploration of this phenomenon. Using grounded theory, a rural school in Indonesia in which the students could achieve relatively high scores in National exam in three academic years was studied. The study focused on how the School-Level Curriculum (SLC, Kurikulum Tingkat SatuanPendidikan, KTSP) policy was interpreted and transferred from the National Education Board to the related school. The study indicated that during the curriculum policy transfer process, a number of significant ideas were adjusted and left out. Based on the findings, this study suggested that educational practitioners should be able to pin down the terms of reference in the SLC policy transfer process in order to reduce misunderstanding, and to do so, they should be equipped with strategies to implement ideas into practice, including the strategies to embed pedagogical theories within the curriculum.